Estrategia para impulsar el consumo de gas natural a través de la venta de calentadores (2023)
From the notion that an innovator idea is that which looks for new ways of doing things, the proposal described in this paper is to impulse the consumption of natural gas throughout three strategies for the sale and installation of gas water heaters in the homes where Gases de Occidente has presence, taking into account that with 4 cubic meters of consumption is the gas based product that most consumption represents. The first strategy is a digital marketing campaign to impulse the sale of water heaters through the program lead by Brilla. The second, is a BTL marketing strategy for the creation of a virtual store where the main product is the water heater , above all this strategy is directed to the other sale channels for this gas base product. Lastly, a communication strategy to strengthen the alliances between Haceb, Gases de Occidente, and the constructors companies for the installation of water heaters in construction sites with the Brilla program.